Congruences and quasiidentities on unars - Kurinnyi, G. Ch. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We establish conditions under which the fact that all congruences of two unars (universal algebras with one unary operation) are convergent implies the convergence of manifolds and quasimanifolds generated by these unars.